(untitled) (African Journal of Biomedical Research, 2019)
Children are highly valued, and childlessness is culturally not acceptable in any typical sub-Saharan African community. Involuntary infertility is associated with significant distress and psychological disturbances, and different psychiatric disorders have been reported among women undergoing fertility treatment. This study aimed to determine prevalence of anxiety and depressive disorders and factors that were predictive of these disorders among women with infertility problem that were attending clinic at a Northeastern Nigerian Teaching Hospital. The study was a cross-sectional, questionnaire-based survey of two hundred and seven adult women on treatment for infertility. Their sociodemographic variables were obtained by the use of pro formal questionnaire and clinical parameters were obtained from their case notes. Hospital anxiety and depression scale was used to determine the presence of anxiety and/or depression using cut-off point of 11. Eighty-five respondents had anxiety and/or depressive disorders which constituted 41.1% of the studied population. Fifty-seven respondents (27.5%) had anxiety disorders while fifty-three (25.6%) had depression and thirty-seven-people (17.9%) had co-morbidity for both disorders. The factors that were predictive of depression were: previous marriage, lack of support, stigmatizing behaviours, tuba-uterine factor as the cause of infertility and surgical method of treatment. Similarly, factors that were predictive of anxiety disorder were: stigmatizing behaviours and lack of supports. Others were long duration of infertility treatment and surgical treatment for infertility as against medical treatment. This study found high prevalence of depression and anxiety disorders among women on treatment for infertility and recommend that more attention be paid to their mental health.